2013
DOI: 10.1017/s0004972713000142
|View full text |Cite
|
Sign up to set email alerts
|

The Strong Dual of Measure Algebras With Certain Locally Convex Topologies

Abstract: For a locally compact group G, we introduce and study a class of locally convex topologies τ on the measure algebra M(G) of G. In particular, we show that the strong dual of (M(G), τ) can be identified with a closed subspace of the Banach space M (G) * ; we also investigate some properties of the locally convex space (M(G), τ).2010 Mathematics subject classification: primary 43A10; secondary 43A15, 46A03, 46H05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We commence this section by recalling the main object of the work which is introduced and studied by the authors in [10].…”
Section: Generalised Functions That Vanish At Infinitymentioning
confidence: 99%
See 1 more Smart Citation
“…We commence this section by recalling the main object of the work which is introduced and studied by the authors in [10].…”
Section: Generalised Functions That Vanish At Infinitymentioning
confidence: 99%
“…Recently in the works [6,10], we studied the first and second duals of measure algebras by the use of the theory of generalised functions which have been introduced and investigated by Sre ȋdr [14] and Wong [15,16]. In those papers we observed that GL 0 (G), the space of all generalised functions that vanishes at infinity, plays a crucial role in our investigation.…”
Section: Introductionmentioning
confidence: 99%